2020
DOI: 10.3389/fneur.2020.00218
|View full text |Cite
|
Sign up to set email alerts
|

A Dose Relationship Between Brain Functional Connectivity and Cumulative Head Impact Exposure in Collegiate Water Polo Players

Abstract: A growing body of evidence suggests that chronic, sport-related head impact exposure can impair brain functional integration and brain structure and function. Evidence of a robust inverse relationship between the frequency and magnitude of repeated head impacts and disturbed brain network function is needed to strengthen an argument for causality. In pursuing such a relationship, we used cap-worn inertial sensors to measure the frequency and magnitude of head impacts sustained by eighteen intercollegiate water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“…The present findings are also consistent with our previous report that changes in brain slow-wave synchrony over one season in water polo players is directly and linearly associated with the magnitude and frequency of head impacts (wCHI) and with frequency taken alone, i.e., without consideration of impact magnitude 47 . ‘Hyperconnectivity’ is theorized as a fundamental, compensatory response of brain functional networks in the face of microstructural perturbation 76 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present findings are also consistent with our previous report that changes in brain slow-wave synchrony over one season in water polo players is directly and linearly associated with the magnitude and frequency of head impacts (wCHI) and with frequency taken alone, i.e., without consideration of impact magnitude 47 . ‘Hyperconnectivity’ is theorized as a fundamental, compensatory response of brain functional networks in the face of microstructural perturbation 76 .…”
Section: Discussionsupporting
confidence: 93%
“…Our group has previously reported on the risks of head impact exposure in water polo, an intense, contact sport that carries a high risk of head, face, and neck injury, particularly at the elite level 43 , 44 . Specifically, we have observed that collegiate water polo players competing at the varsity and club levels sustain regular asymptomatic head impacts 45 , 46 , which may alter brain function in a dose-dependent manner over a competitive season 47 . However, the acute physiological effects of these impacts remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a strength of our study was the inclusion of control athletes that allowed for statistical correction of differences that might exist at baseline and also for natural changes that might occur over the course of a competitive season independent of head impact exposure. Our group recently reported a similar dose-response relationship between head impact exposure sustained by collegiate water polo players, increased coupling in whole-brain slow-rhythm oscillations, and a reduction in inhibitory control that was also suggestive of a shift away from proactive cognitive control strategies ( Monroe et al, 2020 ). Slow (delta rhythm) oscillations measured by electroencephalography are associated with basic homeostatic processes ( Knyazev, 2012 ), which means that the findings of the current study may corroborate those observations and support that repeated, sport-related head impact exposure is capable of disrupting the interface of central and autonomic nervous systems.…”
Section: Discussionmentioning
confidence: 73%
“…Conflicting evidence of the presence of concussion in collegiate players is emerging, 14 but there is a gap in studies on this topic at the international competitive level. 17,18 This discrepancy may be rooted in a lack of recognition of this pathology, because a recent study showed that knowledge on concussions can vary across countries and medical professionals. 19 Therefore, the primary goal of this study was to present the prevalence of concussions in a group of elite-level female water polo players over 10 years.…”
Section: Introductionmentioning
confidence: 99%